KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, KEBIJAKAN DIVIDEN DAN NILAI PERUSAHAAN: INVESTMENT DECISIONS, FUNDING DECISIONS, DIVIDEND POLICY AND COMPANY VALUE - Herawati Herawati; Arie Frinola Minovia; Resti Yulistia M; Egi Hadi Luthfi (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2022)
Every company will maximize its value. This study examines how company value is affected by investment decisions, financing, and dividend policies. The sample for this study is the consumer goods industry, which was selected by purposive sampling. According to this study’s findings, financing decisions have an effect on a company’s value, while investment decisions and dividend policies have no impact on a company’s value.